Treatment of Intravenous Leiomyomatosis with Cardiac Extension following Incomplete Resection. (10th December 2015) - Doyle, Mathew P.; Li, Annette; Villanueva, Claudia I.; Peeceeyen, Sheen C. S.; Cooper, Michael G.; Hanel, Kevin C.; Fermanis, Gary G.; Robertson, Greg
Abstract : Aim . Intravenous leiomyomatosis (IVL) with cardiac extension (CE) is a rare variant of benign uterine leiomyoma. Incomplete resection has a recurrence rate of over 30%. Different hormonal treatments have been described following incomplete resection; however no standard therapy currently exists. We review the literature for medical treatments options following incomplete resection of IVL with CE. Methods . Electronic databases were searched for all studies reporting IVL with CE. These studies were then searched for reports of patients with inoperable or incomplete resection and any further medical treatments. Our database was searched for patients with medical therapy following incomplete resection of IVL with CE and their results were included. Results . All studies were either case reports or case series. Five literature reviews confirm that surgery is the only treatment to achieve cure. The uses of progesterone, estrogen modulation, gonadotropin-releasing hormone antagonism, and aromatase inhibition have been described following incomplete resection. Currently no studies have reviewed the outcomes of these treatments. Conclusions . Complete surgical resection is the only means of cure for IVL with CE, while multiple hormonal therapies have been used with varying results following incomplete resection. Aromatase inhibitors are the only reported treatment to prevent tumor progression or recurrence in patients with incompletely resected IVL with CE.